Dynamics of Gastro-Intestinal Strongyle Parasites in a Group of Translocated, Wild-Captured Asiatic Wild Asses in Kazakhstan - Gliga, Diana S.; Petrova, Natalia; Linnell, John D. C.; Salemgareyev, Albert R.; Zuther, Steffen; Walzer, Chris; Kaczensky, Petra (Frontiers in Veterinary Science, 2020)
Asiatic wild ass (Kulan, Equus hemionus) population range and numbers became severely reduced and a reintroduction project is currently aiming to re-establish a population in the Central Steppe of Kazakhstan. Pre-emptive deworming is often recommended for equid translocations but eliminating parasites prior to translocation could cause disruptions in a balanced host-parasite relationship, adding an additional stressor to an already stressful intervention involving capture, transport, and adaptation to a new environment. Following a disease risk assessment, we decided against pre-emptive deworming and focused on monitoring the first group of nine translocated kulan in a large acclimatization enclosure prior to release. Over the 5-month acclimatization period, we regularly collected fecal samples and analyzed the shedding intensity of gastro-intestinal parasite eggs, obtained time budgets through behavioral observations, and visually assessed body condition. We identified strongyles (Strongylinae and Cyathosominae) and pinworms (Oxyuris equi) in fecal samples. All individuals shed strongyle eggs and two of the nine individuals had higher shedding intensities, but rarely reached levels for which deworming is recommended. All kulan appeared healthy, aggressive interactions were very rare, and time budgets were very similar and dominated by feeding. Our results suggest that in translocation projects where the risk of introducing new parasites is minimal, pre-emptive treatment in wild equids can be replaced with non-invasive monitoring during the acclimatization period. We acknowledge that the small number of kulan, the large size of the enclosure, and the low temperatures during the animals stay in the acclimatization enclosure may all have reduced infestation pressure.